1998
DOI: 10.1200/jco.1998.16.10.3270
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up of relapsed B-cell lymphoma patients treated with iodine-131-labeled anti-CD20 antibody and autologous stem-cell rescue.

Abstract: Myeloablative (131)I-anti-B1 RIT is relatively well tolerated when given with autologous stem-cell support and often results in prolonged remission durations with few late toxicities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
101
0
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(105 citation statements)
references
References 37 publications
2
101
0
2
Order By: Relevance
“…23 The clinical results are impressive, resulting in two antibody conjugates ready for marketing approval from the FDA. RIT using HLA-DR or CD22 as targets for the radioimmunotherapy of NHL are also in earlier phases of clinical trial and the safety and efficacy of these agents is being demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…23 The clinical results are impressive, resulting in two antibody conjugates ready for marketing approval from the FDA. RIT using HLA-DR or CD22 as targets for the radioimmunotherapy of NHL are also in earlier phases of clinical trial and the safety and efficacy of these agents is being demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 21 patients given a therapeutic infusion (19 with progenitor cell rescue), 16 achieved a CR and two a PR, with 81% of patients progression free at a median follow-up of 12 months. Reporting back on long-term follow up of patients in these two trials at a median follow-up of 42 months, 12 of 39 patients remained in continuous complete remission, with those patients with indolent lymphoma gaining most from this approach (Liu et al, 1998). In terms of late toxicity, 60% of patients were found to have an elevated TSH level and two patients had developed myelodysplasia.…”
Section: Incorporation Of Rit Into Myeloablative Regimens With Progenmentioning
confidence: 99%
“…41 With a median follow-up of 42 months, estimated overall survival (OS) and progression-free survival rates (PFS) were 68% and 42%, respectively. Toxicities were minimal when compared with conventional TBI containing transplantation regimens.…”
Section: Bone Marrow Transplantationmentioning
confidence: 99%